(untitled) (GEON Journal (Management, Organizations and Business), 2017)
As a starting point, the paper summarizes the current health situation in Colombia and then continues to evaluate the results of the management of the Venancio Diaz Diaz Hospital with traditional theories and value management. Specifically, the analysis is based on the calculation of traditional indicators and focuses on the analysis of the entity’s EVA for the years 2012-2015. After obtaining the financial results, the paper solves the dilemma of whether these types of companies should always seek economic profitability, or if, on the contrary, a positive social impact frees them from being sustainable when both objectives can not be achieved (Profitability and Social impact). The article in its final part is complemented with an evaluation of the social responsibility of this hospital in the municipality where it exerts influence.